Levelling up academically low-performing students in student-centric education in Singapore: global trend, local policies and future directions. Issue 3 (4th May 2021) - Wang, Li-Yi
ABSTRACT: While Singapore has been consistently ranked in international assessments as one of the world's top education systems, it has a higher percentage of low-performing students compared to other top education systems. Increasingly, the Singapore society is becoming more stratified. In 2011, the Singapore education system revealed a new vision – a student-centric, values-driven education – seemingly expressing the desire to provide all the aid each student needs to succeed. On the National Day Rally speech 2017, Prime Minister Lee Hsien Loong declared the Singapore government's intention to provide all children more support at an earlier age to foster social mobility of the nation. Through glimpsing into education policies pertaining to low-performing students in Singapore and examining empirical evidence from local studies and international literature on low-performing students, the author advocates a shift in paradigm and changes of some long-held assumptions such as one single way to success and early streaming for better differentiation across the three levels of school, education system and society and family to level up low-performing students in the pursuit of the new vision and its goals as well as education equality in the nation.